Anticipatory Mourning and Narrative Meaning-Making in the Younger Breast Cancer Experience: An Application of the Meaning of Loss Codebook - Maria Luisa Martino; Daniela Lemmo; Ines Testoni; Erika Iacona; Laura Pizzolato; Maria Francesca Freda; Robert A. Neimeyer (Behavioral Sciences, 2022)
Breast cancer (BC) in women under 50 is a potentially traumatic experience that can upset a woman’s life during a crucial phase of her lifespan. Anticipatory mourning linked to the diagnosis of BC can produce a series of inevitable losses similar to those of the bereaved. Narration can be one tool to construct meaning, to grow through the experience, and reconfigure time perspectives during and after the illness. The aim of this study was to apply the Meaning of Loss Codebook (MLC) to the narrative context of young women with BC. An ad hoc narrative interview was administered to 17 women at four times during the first year of treatment. A thematic analysis was performed using the MLC, adopting a bottom-up and top-down methodology. The results highlight the MLC’s usefulness in capturing the experiences of the women, allowing for a greater appreciation of the nuances of the meanings embodied in their narratives. The thematic categories grounded in the MLC cover the whole experience of BC during the first year of treatment, attesting to the possibility of extending the use of the MLC to observe the longitudinal elaboration of the psychic experience of BC in addition to its established validity in the context of bereavement and loss.